Symbiont Photosynthesis and Its Effect on Boron Proxies in Planktic Foraminifera. Issue 10 (5th October 2021) - Hönisch, Bärbel; Fish, Carina R.; Phelps, Samuel R.; Haynes, Laura L.; Dyez, Kelsey; Holland, Kate; Fehrenbacher, Jennifer; Allen, Katherine A.; Eggins, Stephen M.; Goes, Joaquim I.
Abstract: Boron proxies in the calcium carbonate shells of planktic foraminifera are sensitive to seawater acidity, but B/Ca ratios and isotopic composition (i.e., δ 11 B) recorded by different foraminifer species grown under identical environmental conditions differ significantly and systematically. Specifically, Globigerinoides ruber displays higher B/Ca and δ 11 B than Trilobatus sacculifer and Orbulina universa . It has been hypothesized that these differences are caused by species‐specific rates of symbiont photosynthesis and habitat depth with greater symbiont photosynthesis elevating the microenvironmental pH of G. ruber relative to T. sacculifer and O. universa . Here we test this hypothesis by applying fast repetition rate fluorometry (FRRF), Chlorophyll a quantification, and symbiont counts in laboratory grown specimens of G. ruber (pink), T. sacculifer and O. universa to study species‐specific differences in symbiont photochemical quantum efficiencies. In addition, we report B/Ca shell profiles measured by laser ablation on the same specimens previously monitored by FRRF, and δ 11 B data of discrete populations of all three species grown under high and low light conditions in the laboratory. While the light experiments document that symbiont photosynthesis elevates pH and/or δ 11 B in the calcifying microenvironment of all three foraminifer species, the FRRF, Chl. a and symbiont abundance data are relatively uniform among the three species and do not scale consistently with intrashell B/Ca, or with observed species‐specific offsets in B/Ca or δ 11 B. Implications of these findings for foraminiferal physiology and biomineralization processes are discussed. Key Points: Symbiont photosynthesis raises pH in the microenvironment of planktic foraminifera Foraminifera species‐specific offsets in boron proxies are the same in laboratory culture and in the natural oceanic environment Symbiont photosynthesis alone does not explain species‐specific boron proxy offsets in planktic foraminifera